Myocarditis and sports in the young: data from a nationwide registry on myocarditis—“MYKKE-Sport” - Schöffl, Isabelle; Holler, Sophia; Dittrich, Sven; Pickardt, Thomas; Opgen-Rhein, Bernd; Boehne, Martin; Wannenmacher, Bardo; Reineke, Katja; Wiegand, Gesa; Hecht, Tobias; Kaestner, Michael; Messroghli, Daniel; et al. (Frontiers in Sports and Active Living, 2023)
Background Myocarditis represents one of the most common causes of Sudden Cardiac Death in children. Myocardial involvement during a viral infection is believed to be higher as a consequence of intensive exertion. Recommendations for return to sports are based on cohort and case studies only. This study aims to investigate the relationship between physical activity and myocarditis in the young. Patient Every patient in the MYKKE registry fulfilling criteria for suspicion of myocarditis was sent a questionnaire regarding the physical activity before, during and after the onset of myocarditis. Method This study is a subproject within the MYKKE registry, a multicenter registry for children and adolescents with suspected myocarditis. The observation period for this analysis was 93 months (September 2013–June 2021). Anamnestic, cardiac magnetic resonance images, echocardiography, biopsy and laboratory records from every patient were retrieved from the MYKKE registry database. Results 58 patients (mean age 14.6 years) were enrolled from 10 centers. Most patients participated in curricular physical activity and 36% in competitive sports before the onset of myocarditis. There was no significant difference of heart function at admission between the physically active and inactive subjects (ejection fraction of 51.8 ± 8.6% for the active group vs. 54.4 ± 7.7% for the inactive group). The recommendations regarding the return to sports varied widely and followed current guidelines in 45%. Most patients did not receive an exercise test before returning to sports. Conclusion Sports before the onset of myocarditis was not associated with a more severe outcome. There is still a discrepancy between current literature and actual recommendations given by health care providers. The fact that most participants did not receive an exercise test before being cleared for sports represents a serious omission.